KPM ProKUS Entrepreneurship Innovation in Cililin Bandung Regency, West Java - Mohammad Erlan Noorfarizal; Nunung Nurwati; Herry Wibowo (SEAN Institute, 2024)
Technological developments have made many changes throughout the world. Developments such as trends in fashion, food, or services have grown rapidly or can be known quickly through existing technology as it is today with the development of this technology can contribute to markets or markets that have not been reached. To be able to support ProKUS, KPM ProKUS is also faced with technological developments that can develop their business even better. This study used a qualitative approach by taking purposive sampling of 3 informants. The data collection methods used in this study were in-depth interviews of informants as well as observations. The results of this study are beneficiary families take advantage of technological developments that can help them make an innovation in their business so that they can develop more